Endoscopic submucosal dissection using an ultrathin endoscope for superficial pharyngeal cancer: a prospective feasibility study (with video) - Muramoto, Takashi; Ohata, Ken; Sakai, Eiji; Sawada, Rikimaru; Takeuchi, Nao; Inamoto, Rin; Kurebayashi, Marie; Takayanagi, Syunya; Kimoto, Yoshiaki; Ishii, Rindo; Nohara, Mako; Liu, Bo; Ono, Kohei; Negishi, Ryoju; Minato, Yohei; Chiba, Hideyuki; Matsuhashi, Nobuyuki (Endoscopy International Open, 2023)
Background and study aims Endoscopic submucosal dissection (ESD) of pharyngeal cancers with conventional endoscopes often is difficult, not only because of the narrow working space, but also because endoscope maneuverability in the pharynx is poor due to interference from the endotracheal tube and/or hyoid bone. However, we hypothesized that those problems could possibly be resolved by use of an ultrathin endoscope for ESD of superficial pharyngeal cancer. The aim of this prospective interventional study was to investigate the feasibility of ESD for superficial pharyngeal cancer using an ultrathin endoscope.Patients and methods This feasibility study was conducted at NTT Medical Center Tokyo between June 2020 and September 2021, and data from a total of 20 consecutively superficial pharyngeal cancers were analyzed. The primary outcome measure was the R0 resection rate. The ESD completion rate, en bloc resection rate, procedure time, and frequency of intraoperative and postoperative adverse events (AEs) were also evaluated as secondary outcome measures.Results Data from 16 patients with 20 lesions were included in the analysis. All of the lesions were successfully resected by ultrathin endoscope ESD, and the en bloc and R0 resection rates were 100 % and 85.0 % (17/20), respectively; the procedure time was 37.8 ± 28.2 minutes. No intraoperative or postoperative AEs were encountered in any cases.Conclusions ESD using an ultrathin endoscope is feasible for superficial pharyngeal cancers and has potential to be a safe and effective treatment option for these cancers.